Ongoing complete response after treatment cessation with dabrafenib, trametinib, and cetuximab as third-line treatment in a patient with advanced BRAFV600E mutated, microsatellite-stable colon cancer: A case report and literature review - Piringer, Gudrun; Decker, Jörn; Trommet, Vera; Kühr, Thomas; Heibl, Sonja; Dörfler, Konrad; Thaler, Josef (Frontiers in Oncology, 2023)
Metastatic BRAFV600E mutated colorectal cancer is associated with poor overall survival and modest effectiveness to standard therapies. Furthermore, survival is influenced by the microsatellite status. Patients with microsatellite stable and BRAFV600E mutated colorectal cancer have the worst prognosis under the wide range of genetic subgroups in colorectal cancer. Herein, we present a patient case of an impressive therapeutic efficacy of dabrafenib, trametinib and cetuximab as later-line therapy in a 52-year old woman with advanced BRAFV600E mutated, microsatellite stable colon cancer. This patient achieved a complete response after one year of triple therapy. Due to skin toxicity grade 3 and recurrent urinary tract infections due to mucosal toxicity a therapy de-escalation to dabrafenib and trametinib was performed and the double therapy was administered for further 41 months with ongoing complete response. Since one year the patient is off therapy and is still in complete remission.